Determinants of Low Birth Weight Among Women Who Gave Birth at Public Health Facilities in North Shewa Zone: Unmatched Case-Control Study - Berhanu Senbeta Deriba; Kemal Jemal (SAGE Publishing, 2021)
Globally, more than 20 million newborns are born with low birth weight (LBW) every year. Most of the LBW occurs in low- and middle-income countries. It is the most critical risk of neonate mortality. Therefore, this study aims to identify determinants of low birth weight among women who gave birth in public health facilities in the North Shewa zone. Institutional-based unmatched case-control study was conducted from February to June 2020 to select 180 cases and 380 controls. Interviewer-administered questionnaire was used to collect data. Data were entered through EPI Info and exported to Statistical Package for Social Science (SPSS) for analysis. Text, percentage and tables were used to present data. Bivariate and multivariate logistic regression analyses were performed to see the association and adjusted odds ratios with 95% confidence interval (CI), and P -value < .05 was considered to declare statistical significance. Lack of nutritional counseling (adjusted odds ratio [AOR] = 2.14; 95% CI = [1.13, 4.04]), unable to take iron-folate supplement (AOR = 2.3.78; 95% CI = [2.1, 6.85]), insufficient additional meal in take (AOR = 6.93; 95% CI = [3.92, 12.26]), restriction of foods (AOR=2.29; 95% CI =[1.81, 4.09]), maternal mid upper arm circumference (MUAC) < 23 cm (AOR=2.85; 95% CI = [ 1.68, 4.85]), maternal height ≤155 cm (AOR=3.58; 95% CI = [1.92, 6.7]), anemia (AOR = 2.34; 95% CI = [1.21, 4.53]), pregnancy-related complications (AOR=3.39; 95% CI = [2.02, 5.68]), and alcohol drinking during pregnancy (AOR = 2.25; 95% CI = [1.24, 4.08]) were significantly associated with LBW. Nutritional counseling, iron-folate supplementation, additional meal intake, restriction of some foods in pregnancy, MUAC of the mother, maternal stature, maternal anemia status, pregnancy-related complications, and a history of alcohol drinking during pregnancy were identified as determinants of low birth weight. The intervention-targeted nutritional counseling, early detection and treatment of anemia, and behavioral change communication to pregnant women are mandatory.